THE EDUCATIONAL SYSTEM OF THE USA: STRUCTURE, TRADITIONS OF MANAGEMENT, FEATURES OF HIGHER EDUCATION - Bratko, Mariia (Educological discourse, 2017)
This article represents the results of scientific research of the American education system. The American educational system is an example of a decentralized educational system with an appropriate structure and management content. It is difficult to study, because it has a special structure, different subordination and accountability, different sources of funding, is multilevel. The American educational system is revealed that the current state of the American educational system is determined by the historical development of the country, socio-cultural and economic realities. The essential features of a successful model of higher education are investigated. It is autonomous, multi-level, versatile, flexible. It is concluded that managerial decisions in the field of education are based on the results of multidimensional studies on its state and consistent with the needs of civilization advancement. Positive aspects of higher education in the USA that are worth adaptation and usage in the education field of Ukraine have been determined. The author of the article think, that implementation of the research the positive foreign experience in strategy of education management adoption and the higher school organisation will help the Ukraine ones to find own way of rational and effective modernization of education system.